2020
DOI: 10.1093/noajnl/vdaa161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates for immune checkpoint therapy: significance for CNS malignancies

Abstract: Immune checkpoint inhibitors (ICI) have revolutionized the field of cancer immunotherapy. Most commonly, inhibitors of PD-1 and CTLA4 are used having received approval for treatment of many cancers like melanoma, non-small cell lung carcinoma (NSCLC), and leukemia. In contrast, to date clinical studies conducted in patients with central nervous system (CNS) malignancies have not demonstrated promising results. However, patients with CNS malignancies have several underlying factors such as treatment with suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…A recent report demonstrated that fecal transplants from responder donors is safe and feasible, but correlating tumor responses to the influx of T-cells and other immune cells is still somewhat contentious. 38 Interestingly, a peripheral immune response is being considered as a potential biomarker to assess intratumoral immune responses, 39 but studies need to be performed to assess feasibility and validation of this approach. Lastly, the mouse microbiome is also a positive responder to anti-PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that fecal transplants from responder donors is safe and feasible, but correlating tumor responses to the influx of T-cells and other immune cells is still somewhat contentious. 38 Interestingly, a peripheral immune response is being considered as a potential biomarker to assess intratumoral immune responses, 39 but studies need to be performed to assess feasibility and validation of this approach. Lastly, the mouse microbiome is also a positive responder to anti-PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…Although immune checkpoint inhibitors (ICIs) have been written into the clinical application guidelines for various recurrent malignant tumors and advanced cancers, they are only effective for a long time in a part of the population, and drug resistance or immune-related adverse events (irAEs) may occur in another part of the population [3]. Currently, there are two main classes of immune checkpoint inhibitors: antibodies targeting cytotoxic T-lymphocyte antigen-4 (CTLA-4) and antibodies targeting programmed cell death protein-1 (PD-1) and its ligand programmed death receptor ligand-1 (PD-L1) [37]. Ipilimumab, the rst ICIs approved for marketing by the FDA, is an antibody targeting CTLA-4 and is primarily used for the treatment of melanoma [38].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies are often capable of showing whether patients are experiencing a response to the intervention. However, imaging in brain tumor studies can be complicated as it can be quite difficult to distinguish between tumor progression and response to therapy (pseudo-progression) (122). Therefore, incorporating other imaging studies such as positron emission tomography (PET) into brain tumor immunotherapy clinical trials may be complementary and help confirm patient response to treatment (123)(124)(125).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Previous studies have shown that looking at peripheral markers of immune response such as the clonal expansion of T cells, expression of specific chemokine receptors, and levels of IFN-gamma can potentially determine whether a patient is experiencing a response to immunotherapy ( 122 ). In patients with GBM, it has been observed that an enhanced expression of IFN-gamma has been associated with better patient outcomes, while the IL-6 axis specifically has been associated with both increased tumor growth and expression of an M2-like myeloid phenotype ( 32 , 122 , 127 ). If patients experience an immune response as shown by markers within the peripheral blood yet fail to meet the primary endpoints of a trial, additional treatments may be needed to enhance either the trafficking of peripheral immune cells to the brain tumor or suppress the hostile TME.…”
Section: Clinical Trialsmentioning
confidence: 99%